Um território (re)apropriado?: a dinâmica territorial da cozinha em meio a relações sociais de gênero e raça - Felipe Gouvêa Pena (2017)
This dissertation aimed to understand how the domestic kitchen is territorialized in the middle of social relations of gender and race. In a qualitative approach, the study was based on a combination of three data gathering techniques: the semi-structured interview, the word evocation test and the photoelicitation technique. The collected material was organized and categorized according to French discourse analysis, with a series of procedures that consider the explicit, implicit and silenced aspects in the discourses (FARIA, 2009). There was considered as a research subjects: housewives, maids and employers, starting from the assumption that in different ways these individuals contribute to the established problematization. Domestic cooking, as a territory, perhaps is the clearest example of gender division in the household, because it has always been considered a feminine "place." Historically located in the back of the houses, the kitchen was the work place of the cooks, usually black, and the housewife, and therefore, without value. The organization of this space does not only refer to a stronghold in which the materialization of social interactions occurs, but also it own tends to structure such interactions (LEFEBVRE, 1991). Therefore, it is not possible to speak in neutrality, at the material and symbolic levels, in this or any other space, since it is demarcated politically and ideologically, stage of coercions of a group of dominant in relation to a group dominated in different instances. The current "gastronomization" movement of daily food values domestic cuisine in the media, in a process of endogenous of the aesthetics of daily life (BARBOSA, 2012). The argument was defended that such valorization of the kitchen and, consequently, of the act of cooking, it reaffirms territorially, but hide issues of gender and race. Men, historically associated with public space, has appropriated the domestic cooking in the midst of media discourses of the gourmet movement, which value, exalt and give it the title of "owner" of the kitchen. The results of the research strengthen the idea that the territorial dynamics of this domestic space is permeated by the social relations of gender and race and that, in fact, there is a process of (re)appropriation of this territory, mainly from the symbolic point of view.